Design Method for Twisting and Reducing Tooth Surfaces of Herringbone Gears for Form Grinding - Zhang Xin; Liu Xinrong; Wang Huipeng (Jixie chuandong)
Tooth surface twisting is a kind of processing error generated when the spiral herringbone gear is formed and grinded. In order to reduce the tooth surface distortion and improve the grinding accuracy, a gear reverse twisting processing calculation method is proposed based on reverse thinking to reduce the processing error caused by the tooth surface distortion. According to the meshing coordinate system of the shaping and grinding herringbone gear space, the contact line at multiple positions of the standard gear tooth surface, tooth surface twisting and tooth surface anti-twisting is solved, and the reverse distortion model of the tooth surface of the herringbone gear is established by calculating the curvature of the tooth surface method and the amount of spiral modification. The contact line optimization of the gears before and after the shaping is combined with the Monte Carlo method; and the transmission error of the tooth surface anti-twisting and the tooth surface twisting; and also the tooth surface contact stress are analyzed by the finite element method. Finally, the dynamic characteristics of the tooth surface twist and the tooth surface anti-twist after the shape are compared. The results show that the tooth surface anti-twisting machining can effectively reduce the error of the tooth surface processing principle of the herringbone gear and improve the grinding accuracy of the herringbone gear.